Α-SpecTrim: A new application designed for reproducing alpha-particle spectra. (July 2022) - Fernández Timón, A.; Jurado Vargas, M.; Peña Morante, C.; Sánchez-Oro Calvo, J.
Abstract: In this work, we introduce a new software application developed to reproduce α-particle spectra measured with silicon detectors. It takes into consideration the main physical processes involved in the interaction of alpha particles with the source and the detector. This application is considerably more user-friendly than multipurpose codes, being also the runtimes to obtain a spectrum much lower. It makes use of the TRIM simulation code for tracking alpha particles in the source and the detector entrance window. Concerning to the response function of a silicon detector, the contribution of electronic excitation and ionization produced by the alpha particles is also obtained by simulation, while the electron-hole pair statistics and the broadening produced by the amplifier system (electronic chain) are included as convolutions of theoretical functions. The code α-SpecTrim is written in Python 3 language using Flask framework, so it can be run in every PC or laptop. It is free and can be provided if requested to the authors. Highlights: Development of a new application for reproducing alpha-particle spectra. The application is written in Python language. Interface very easy to use and can be run on multiple platforms. The simulations required into the application are performed by the well-known TRIM code. This application can be an useful tool in alpha-particle spectrometry.